Financial Trend Analysis of Gaurishankar Multiple Campus - K.C, Shanta Bahadur; Shrestha, Karuna (GS Spark: Journal of Applied Academic Discourse, 2024)
The study presents a financial trend analysis of Gaurishankar Multiple Campus (GSMC) Charikot, Dolakha, focusing on income and expenditure patterns, and per-student investment costs over the four years period. Using a descriptive research design, the study analyzes financial statements and related data over the period of four years as a result, it carries out relevant findings regarding the campus's financial condition. The research indicates significant trends in income and expenditure patterns, emphasizing both areas of financial efficiency and prioritizing its further improvement. The findings show that, needs to be included the particular aspects found through research of the campus's financial management are strong, it is to be mentioned the areas that need thoughtful attention to improve financial performance. The financial analysis of GSMC presents recurring losses because routine expenses consistently exceed student fee income. Despite increased fee income, campus administration is struggling to meet regular costs due to quicker expense increases. GSMC's focus on alternate revenue streams reflects its efforts to maintain financial stability. Increased enrollment improves cost efficiency while raising concerns about educational quality. Investments in teaching excellence, including increased teacher salary, underscore GSMC's dedication to academic standards. To maintain sustainability, the campus must improve financial management, explore new revenue streams, and reduce operational expenditures. Comprehensive studies are required to ensure long-term financial stability and educational Advancement.